A new method for pulse analysis of driftless-gas proportional scintillation counters - Simões, P. C. P. S. (2003)
A new method for pulse analysis of driftless-gas proportional scintillation counters (GPSCs) is presented. With this method the requirement for additional analog or digital signal time-analysis and pulse-amplitude correction currently used is eliminated. In contrast to conventional- and driftless-GPSCs that have always relied on long shaping-time constants (several [mu]s), the use of very short linear amplifier shaping-time constants (~50 ns) enables pulse shapes to closely represent the scintillation light-pulse time-profile. Since the number of detected photons in the photosensor increases continuously with depth due to the increase in the solid angle subtended by the photosensor, a maximum is achieved when the primary electron cloud is closest to the anode. This maximum depends only on the number of primary electrons in that cloud, regardless of where the X-ray absorption took place, and is proportional to the X-ray energy.